Freezing method affects the concentration and variability of urine proteins and the interpretation of data on microalbuminuria - Schultz, C; Dalton, R; Turner, C; Neil, H; Dunger, D (2000)
Aims. Microalbuminuria and, to a lesser extent, renal tubular proteins are widely used in the early detection of incipient nephropathy in diabetes mellitus. Recent reports have indicated detrimental effects of storage at - 20°C on urine proteins. This study investigated the effects of storage on the measurement of urine proteins and discusses implications for the interpretation of data. Methods. Two-hundred and sixty-eight specimens, collected from children with Type 1 diabetes, split into duplicate aliquots and stored at -20°C and -70°C, respectively, for 6-8 months, were analysed for albumin, retinol binding protein, N-acetyl glucosaminidase and creatinine, in the same assays to eliminate inter-assay variability. Two independent non-diabetic cohorts of children provided urine specimens, which were stored at -20°C for one cohort and -70°C for the other, to determine normal ranges for urine proteins. Results. Storage at -20°C led to a variable underestimation of all three urine proteins in 20% of specimens. Creatinine was unaffected. This underestimation was greater in more concentrated urine (r2 = 0.38, P < 0.001, n = 262). Consequently storage at -20°C increased the variance of the albumin/creatinine ratio more than the variance of albumin concentration. Temperature of storage affected the normal range, which was 0.1-2.1 mg/mmol at -20°C compared to 0.3-3.1 mg/mmol at -70°C. The prevalence of microalbuminuria (> 2SD above the geometric mean in non-diabetic specimens stored at -20°C) was 27% after storage at -70°C vs. 24% after -20°C. The prevalence of microalbuminuria (> 2SD above the geometric mean in nondiabetic specimens stored at -70°C) was 21% after storage at -70°C vs. 17% after -20°C. Conclusions. Urine proteins are significantly but variably underestimated after storage at -20 °C. These effects account for increased variance and differences in the normal range, but have less effect on the detection of microalbuminuria than might be predicted.